"Yes and. . ., but wait. . ., heck no!": A socially situated cognitive approach towards understanding how startup entrepreneurs process critical feedback. (3rd September 2021) - Kaffka, Gabi A.; Singaram, Raja; Kraaijenbrink, Jeroen; Groen, Aard J.
ABSTRACT: We examine sensebreaking, a meaning void, that entrepreneurs experience due to critical feedback from early stakeholders using the socially situated cognition perspective. We show that sensebreaking aids novel sensemaking via three mechanisms—redirecting, reframing, and questioning—through longitudinal analysis of weekly diary reports that we collected from 30 entrepreneurs for one year. We describe the cognitive changes due to novel sensemaking. We derive a process model that illustrates how sensebreaking-sensemaking iterations over time effect changes to the shared cognition between entrepreneurs and their stakeholders while driving opportunity development. We advance the opportunity coconstruction literature by adding microlevel understanding of stakeholder interactions and explicating their effects on entrepreneurial cognition.